Stratégies discursives: discours direct, discours indirect, discours indirect libre - Guentchéva , Zlatka (Neophilologica, 2005)
The author of the article discusses the possibilities of connecting various types of speech (direct speech, indirect speech, free indirect speech) in a textual sequence. The construction of a textual sequence depends on the time references and other related parameters. In case of the direct speech a reference is connected with a single event described by a speaker whereas in case of the indirect speech it becomes assigned to a specific speaker.